Karyopherin Msn5 is involved in a novel mechanism controlling the cellular level of cell cycle regulators Cln2 and Swi5. Issue 5 (4th March 2019) - Quilis, Inma; Taberner, Francisco J.; Martínez-Garay, Carlos A.; Alepuz, Paula; Igual, J. Carlos
ABSTRACT: The yeast β-karyopherin Msn5 controls the SBF cell-cycle transcription factor, responsible for the periodic expression of CLN2 cyclin gene at G1/S, and the nuclear export of Cln2 protein. Here we show that Msn5 regulates Cln2 by an additional mechanism. Inactivation of Msn5 causes a severe reduction in the cellular content of Cln2. This occurs by a post-transcriptional mechanism, since CLN2 mRNA level is not importantly affected in asynchronous cultures. Cln2 stability is not significantly altered in msn5 cells and inactivation of Msn5 causes a reduction in protein level even when Cln2 is stabilized. Therefore, the reduced amount of Cln2 in msn5 cells is mainly due not to a higher rate of protein degradation but to a defect in Cln2 synthesis. In fact, analysis of polysome profiles indicated that Msn5 inactivation causes a shift of CLN2 and SWI5 mRNAs from heavy-polysomal to light-polysomal and non-polysomal fractions, supporting a defect in Cln2 and Swi5 protein synthesis in the msn5 mutant. The analysis of truncated versions of Cln2 and of chimeric cyclins combining distinct domains from Cln2 and the related Cln1 cyclin identified an internal region in Cln2 from 181 to 225 residues that when fused to GFP is able to confer Msn5-dependent regulation of protein cellular content. Finally, we showed that a high level of Cln2 is toxic in the absence of Msn5. In summary, we described that Msn5 is required for the proper protein synthesis of specific proteins, introducing a new level of control of cell cycle regulators. Graphical Abstract: uf0001